1992
DOI: 10.1113/jphysiol.1992.sp019101
|View full text |Cite
|
Sign up to set email alerts
|

Direct modulation of GABAA receptor by intracellular ATP in dissociated nucleus tractus solitarii neurones of rat.

Abstract: SUMMARY1. Effect of intracellular ATP on Cl-current (I1c) mediated by the GABA (yaminobutyric acid) receptor subtype, GABAA, was studied in dissociated nucleus tractus solitarii (NTS) neurones using the whole-cell mode of patch clamp. A concentration-jump technique termed 'Y tube' was used to rapidly apply agents externally. Dissociated neurones were obtained from 1-to 3-week-old rats.2. When the patch-pipette solution contained 2 mM-ATP, the amplitude of Ic elicited by 10-5 M-GABA did not show any time-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 43 publications
3
45
1
Order By: Relevance
“…Since the GABAA response recorded by the use of conventional whole-cell mode of patch-clamp technique decreases time-dependently, 5 mM MgATP was added to the internal solution to prevent the sensitivity-loss for the affinity of GABAA receptor (run-down) (Chen et al, 1990;Shirasaki et al, 1992). When this was done, the GABA responses were maintained for more than 1 h and increased in a sigmoidal fashion with increase in the concentration of GABA.…”
Section: Resultsmentioning
confidence: 99%
“…Since the GABAA response recorded by the use of conventional whole-cell mode of patch-clamp technique decreases time-dependently, 5 mM MgATP was added to the internal solution to prevent the sensitivity-loss for the affinity of GABAA receptor (run-down) (Chen et al, 1990;Shirasaki et al, 1992). When this was done, the GABA responses were maintained for more than 1 h and increased in a sigmoidal fashion with increase in the concentration of GABA.…”
Section: Resultsmentioning
confidence: 99%
“…Suppression of the GABA response involved a dephosphorylation process Previous results suggested that intracellular Ca2+ suppresses the GABA response in the hippocampal cell by activating a phosphatase (Chen et al 1990; see, however, Shirasaki, Aibara & Akaike, 1992). We examined the possible involvement of dephosphorylation in the NMDAinduced suppression of the GABA response.…”
Section: Resultsmentioning
confidence: 99%
“…9 To determine if run-down of GABA-evoked currents contributed to the differences in EC 50 between NT and HT rats, GABA was applied (1 mmol/L, 2-second duration) at the onset of a recording and every 5 minutes for 25 minutes. The peak current density after 25 minutes of recording was 94Ϯ11% of the value obtained at the onset of the recording in NT rats (nϭ8) and 95Ϯ3% in HT rats (nϭ3) (PϾ0.05).…”
Section: Time-dependent Changes In Gaba Receptor-evoked Responsesmentioning
confidence: 99%